Minireview: Challenges and opportunities in development of PPAR agonists - Wright, Matthew B; Bortolini, Michele; Tadayyon, Moh; Bopst, Martin (Molecular endocrinology (Baltimore, Md.), 2014)
The clinical impact of the fibrate and thiazolidinedione drugs on dyslipidemia and diabetes is driven mainly through activation of two transcription factors, peroxisome proliferator-activated receptors (PPAR)-α and PPAR-γ. However, substantial differences exist in the therapeutic and side-effect profiles of specific drugs. This has been attributed primarily to the complexity of drug-target complexes that involve many coregulatory proteins in the context of specific target gene promoters. Recent data have revealed that some PPAR ligands interact with other non-PPAR targets. Here we review concepts used to develop new agents that preferentially modulate transcriptional complex assembly, target more than one PPAR receptor simultaneously, or act as partial agonists. We highlight newly described on-target mechanisms of PPAR regulation including phosphorylation and nongenomic regulation. We briefly describe the recently discovered non-PPAR protein targets of thiazolidinediones, mitoNEET, and mTOT. Finally, we summarize the contributions of on- and off-target actions to select therapeutic and side effects of PPAR ligands including insulin sensitivity, cardiovascular actions, inflammation, and carcinogenicity.